Estimation of effect of physical training on forming of personal qualities. - Lisak V.N (Kharkov National Pedagogical University, 2010)
Directions of forming of personal qualities of students under effect of exercises by physical training and sports are construed. 125 students have taken part in questioning. It is exhibited, that to growth of a level of sports skill there are fluctuations in frame of the personality of students. Fluctuations are mapped in qualitative indexes of developing individually - psychological properties. It is indicated, that exercises by sports are the remedy of raise of social activity of students. They influence character traits, labour activity, intellectual and intellectual qualities.